Ta có: \frac{a^{2}}{3}+ b^{2}+c^{2}> ab+bc+ac \Leftrightarrow \frac{a^{2}}{3}+b^{2}+c^{2}-a(b+c)-bc> 0$\Leftrightarrow \frac{a^{2}}{3}+(b+c)^{2}+a(b+c)-3bc> 0 (*) Thay bc=\frac{1}{a} ta được:(*)\Leftrightarrow \frac{a^{2}}{3}+(b+c)^{2}+a(b+c)-\frac{3}{a}>0\Leftrightarrow a(b+c)^{2}-a^{2}(b+c)+\frac{a^{3}}{3}-3>0 $Đặt $b+c=x$ ta có: $ax^{2}-a^{2}x+\frac{a^{3}}{3}-3>0 $ với mọi x$\Leftrightarrow \Delta = a^{4}-4a(\frac{a^{3}}{3}-3)<0\Leftrightarrow a^{4}-\frac{4a^{4}}{3}+12a<012a(36-a^{3}) <0$ đúng vì $a^{3}>36\Rightarrow $ đpcm
Ta có:
\frac{a^{2}}{3}+ b^{2}+c^{2}> ab+bc+ac \Leftrightarrow \frac{a^{2}}{3}+b^{2}+c^{2}-a(b+c)-bc> 0$\Leftrightarrow \frac{a^{2}}{3}+(b+c)^{2}
-a(b+c)-3bc> 0 (*)
Thay bc=\frac{1}{a}
ta được:(*)\Leftrightarrow \frac{a^{2}}{3}+(b+c)^{2}+a(b+c)-\frac{3}{a}>0
\Leftrightarrow a(b+c)^{2}-a^{2}(b+c)+\frac{a^{3}}{3}-3>0 $Đặt $b+c=x$ ta có: $ax^{2}-a^{2}x+\frac{a^{3}}{3}-3>0 $ với mọi x$\Leftrightarrow \Delta = a^{4}-4a(\frac{a^{3}}{3}-3)<0\Leftrightarrow a^{4}-\frac{4a^{4}}{3}+12a<0
12a(36-a^{3}) <0$ đúng vì $a^{3}>36\Rightarrow $ đpcm